On-farm performance of tomato cultivar Utkal Raja under off-season rainfed conditions of Eastern Ghats Highland Zone of Odisha - Maharana, Jyotshnarani; Behera, S.K; Jakhar, Praveen; Dass, Anchal (Annals of Agricultural Research, 2016)
A study was conducted at Krishi Vigyan Kendra, Semiliguda in Eastern Ghats Highland zone ofÂ Odisha for three consecutive rainy seasons of 2011, 2012 and 2013 to evaluate the performance ofÂ tomato variety Utkal Raja at farmers’ field under rainfed conditions. Front line demonstrations (FLDs)Â were conducted with scientific package of off-season tomato cultivation. Utkal Raja variety of tomatoÂ was found superior over farmers’ existing practices with local varieties. Utkal Raja with improvedÂ production technologies in FLDs, increased mean fruit yield by 22% over existing farmers’ practiceÂ with only 1273/ha extra expenditure on inputs. The mean extension gap (3.75 t/ha) and meanÂ incremental B:C ratio (30.7) is sufficiently high to motivate farmers for adoption of Utkal Raja in offseasonÂ tomato production technology